TAX AVOIDANCE : BOARD CHARACTERISTICS, FINANCIAL DISTRESS, DAN COMPANY SIZE - Makatita, Grace Gloria; Syahzuni, Barlia Annis (E-Jurnal Akuntansi TSM, 2025)
This study aims to analyze the influence of corporate governance (board independence, board size, female directors) and company characteristics (financial distress, company size) on tax avoidance in energy sector companies in Indonesia. This study uses a quantitative approach with panel data from 44 energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period (176 observations). Tests were conducted using a Random Effects model, with tax avoidance proxied by the Effective Tax Rate (ETR), and financial distress measured using the Altman Z-Score. The results show that financial distress has a significant negative effect on tax avoidance, while company size has a significant positive effect. Corporate governance variables do not show a significant effect. These findings are useful for regulators in increasing oversight of large companies and reviewing governance effectiveness. For companies, these results emphasize the importance of board quality, while for investors, company size can be an indicator of tax avoidance risk.